2013
DOI: 10.1371/journal.pone.0079404
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Phytophagous Insects with Salmonella enterica on Plants and Enhanced Persistence of the Pathogen with Macrosteles quadrilineatus Infestation or Frankliniella occidentalis Feeding

Abstract: Recently, most foodborne illness outbreaks of salmonellosis have been caused by consumption of contaminated fresh produce. Yet, the mechanisms that allow the human pathogen Salmonella enterica to contaminate and grow in plant environments remain poorly described. We examined the effect of feeding by phytophagous insects on survival of S. enterica on lettuce. Larger S. enterica populations were found on leaves infested with Macrosteles quadrilineatus. In contrast, pathogen populations among plants exposed to Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…In the case of phytobacterial pathogens, transmission can occur by physical contact of plant tissues with contaminated mouthparts, legs, and bodies or deposition of contaminated saliva or feces on leaf surfaces (18,40). Previous studies demonstrated that 50% of Frankliniella occidentalis, M. quadrilineatus, and M. persicae insects became contaminated with S. enterica from feeding on contaminated plant material (13). Furthermore, S. enterica was isolated from both tomato and lettuce plants in areas damaged by contaminated F. occidentalis, which had previously fed on S. enterica-inoculated green beans (41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of phytobacterial pathogens, transmission can occur by physical contact of plant tissues with contaminated mouthparts, legs, and bodies or deposition of contaminated saliva or feces on leaf surfaces (18,40). Previous studies demonstrated that 50% of Frankliniella occidentalis, M. quadrilineatus, and M. persicae insects became contaminated with S. enterica from feeding on contaminated plant material (13). Furthermore, S. enterica was isolated from both tomato and lettuce plants in areas damaged by contaminated F. occidentalis, which had previously fed on S. enterica-inoculated green beans (41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S. enterica was isolated from both tomato and lettuce plants in areas damaged by contaminated F. occidentalis, which had previously fed on S. enterica-inoculated green beans (41). Also, the presence of M. quadrilineatus and feeding damage of F. occidentalis enhanced the longevity of S. enterica on lettuce (13). In this study, both internally and externally contaminated M. quadrilineatus and M. persicae insects were able to transmit S. enterica to noninoculated leaves or liquid diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the aggregation behavior and short-distance dispersal on lettuce (32) indicate that S. enterica-contaminated leafhoppers could contaminate multiple leaves and adjacent plants even in a short period. Additionally, the fact that infestation with M. quadrilineatus enhanced the epiphytic survival of S. enterica on lettuce leaves (8) and that its honeydew can serve as a growth medium for the bacterium (J. P. Soto-Arias, R. L. Groves, and J. D. Barak, presented at the Food Research Institute annual meeting, Madison, WI, 21 to 22 May 2014) increases the chances of insect contamination, and therefore further dispersal of the pathogen on and among plants. Thus, this study further confirms that the most likely mode of transmission of ingested S. enterica by M. quadrilineatus implicates survival of the pathogen during passage through the alimentary canal and release in the environment in contaminated honeydew.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that M. quadrilineatus can become contaminated with S. enterica after feeding on contaminated plant material, and plant infestation with these insects enhanced the persistence of the pathogen on lettuce (8). M. quadrilineatus can also transmit externally attached and ingested bacteria to noninoculated leaves or artificial diets, thereby serving as vectors of S. enterica (6).…”
mentioning
confidence: 99%